Eka Juniani, Ni Putu (2016). The Effect of Think Pair Share Technique on the Students’ Achievement Motivation and Writing Competency of the Seventh Grade Students of SMP N 2 Kuta Selatan - ., NI PUTU EKA JUNIANI; ., DR. NI MADE RATMININGSIH, M.A.; ., DR. LUH PUTU ARTINI, M.A. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
This study aimed at: (a) finding out whether or not there is a significant effect of Think Pair Share Technique on the students? achievement motivation, (b) finding out whether or not there is a significant effect of Think Pair Share Technique on the students? writing competency, (c) finding out whether or not there is a simultaneous significant effect of Think Pair Share Technique on the students? achievement motivation and writing competency. This study was an experimental study which use Post-test only control group design. The population of the study was 10 classes of which consisted of 380 students and four classes were selected as the sample of the study which consisted of 152 students. The data of the study was analyzed by using one-way ANOVA and MANOVA. The result of the data showed that there is a significant effect of Think Pair Share Technique on the students? achievement motivation, there is a significant effect of Think Pair Share Technique on the students? writing competency, and there is a simultaneous significant effect of Think Pair Share Technique on the students? achievement motivation and writing competency.Kata Kunci : Think Pair Share Technique (TPS), Achievement Motivation, Writing Competency Penelitian ini bertujuan untuk: (a) mencari tahu pengaruh teknik Think Pair Share terhadap motivasi belajar siswa, (b) mencari tahu pengaruh teknik Think Pair Share terhadap kemampuan menulis siswa,, (c) mencari tahu pengaruh teknik Think Pair Share terhadap motivasi belajar siswa dan kemampuan menulis siswa. Penelitian ini adalah penelitian experimen yang hanya menggunakan desain Post-test only control group. Populasi penelitian ini yaitu 10 kelas yang terdiri dari 380 orang murid dan 4 kelas di pilih sebagai sampel yang terdiri dari 152 murid. Data dari penelitian ini di analisis dengan menggunakan one-way ANOVA dan MANOVA. Hasil dari data yang telah di dapat menunjukkan bahwa terdapat pengaruh teknik Think Pair Share terhadap motivasi belajar siswa, terdapat pengaruh teknik Think Pair Share terhadap kemampuan menulis siswa, dan terdapat pengaruh teknik Think Pair Share terhadap motivasi belajar siswa dan kemampuan menulis siswa.keyword : Teknik Think Pair Share (TPS), Motivasi belajar, Kemampuan menulis